Party system closure and openness: conceptualization, operationalization and validation - Casal Bertoa, Fernando; Enyedi, Zsolt (SAGE, 2016)
The degree of closure of the governmental arena is a central aspect of the stabilization of party systems, and yet little systematic effort has been devoted to its operationalization. The article proposes a new index, examines its reliability and validity, and reports the ranking of 60 party systems. By redefining the units of measurement we suggest new indicators that are uniform and transparent in their logic of construction, can be applied both to specific government-changes and to time periods, and are sensitive to the degree of change. The article finds a hierarchy among the components of party system closure, dominated by coalition formula. While new and established democracies can both produced closed patterns, the analysis of inter-war European party systems shows that closed systems are less prone to authoritarian takeover. The article demonstrates the power of inertia: the completely closed configurations stand out as the most durable ones.